Self-Criticism and Self-Compassion in Adolescents: Two Forms of Self-Relating and Their Implications forPsychopathology and Treatment - Salvador, Maria do Céu (2017)
Different ways of relating to oneself are linked with distinctive mental health outcomes: shame and self-criticism underpin a variety of psychological disorders, while self-compassion stands as a resource or protective factor related to psychological well-being, resilience and positive development. Despite the fact that compassion-based interventions have flourished over the last decade, holding promising results for adult populations, the integration of compassion in adolescent psychotherapy remains scarcely discussed. The present paper endorses an evolutionary model of human development and psychopathology for outlining our basic affect regulation systems, describing their functioning and development in the context of adolescence. The role of shame and self-criticism as transdiagnostic features is discussed for different forms of adolescent psychopathology, and the process of promoting self-compassion is summarized under specific compassion-based therapeutic models.